2019
DOI: 10.5137/1019-5149.jtn.23307-18.3
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode recording for deep brain stimulation of the subthalamic nucleus in patients with advanced parkinson’s disease: advantage or loss of time?

Abstract: AIM: To investigate the effect of using microelectrode recording (MER) on the length of time required to carry out a deep brain stimulation (DBS) procedure of the subthalamic nucleus in patients with Parkinson's disease (PD). MATERIAL and METHODS: The time required to include MER in the DBS operation was calculated for the first and second sides in 24 patients with PD. The number of microelectrodes used on each trajectory for the first and second sides, and the percentage of permanent electrodes implanted on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…MER will likely continue to be an important technique in places that do not yet have access to more advanced imaging techniques ( 39 , 40 ). Although the use of MER does extend the length of the DBS procedure ( 41 ), MER frequently provides important physiologic information that results in lead adjustments up to 20–40% of the time, which can be especially important in instances when there is significant brain shift following preoperative imaging ( 42 , 43 ).…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%
“…MER will likely continue to be an important technique in places that do not yet have access to more advanced imaging techniques ( 39 , 40 ). Although the use of MER does extend the length of the DBS procedure ( 41 ), MER frequently provides important physiologic information that results in lead adjustments up to 20–40% of the time, which can be especially important in instances when there is significant brain shift following preoperative imaging ( 42 , 43 ).…”
Section: Dbs Targeting Strategiesmentioning
confidence: 99%
“…Today, advanced magnetic resonance technologies allow for direct targeting of STN. However, MER prolongs the surgical procedure to a certain extent (12). While some studies indicated that the latter increases the ICH rates, there are others reporting otherwise (3,9,27).…”
Section: █ Conclusionmentioning
confidence: 99%
“…This includes advances in the skills of the neurosurgeon, such as skin incision, drilling, and suture, and the rapid assessment of microelectrode recording when inserting intracranial electrodes. In addition, fast and accurate reading of the microelectrode recording is important for the proper placement of the intracranial electrode ( Kocabicak et al, 2019 ; Soares et al, 2019 ; Reddy et al, 2020 ). We consider that the accumulation of experience and the technological advances in DBS surgery could shorten the operation time and reduce the complications and infections rates.…”
Section: Discussionmentioning
confidence: 99%